Meningkatkan Kemampuan Pemahaman dan Komunikasi Matematis Siswa Sekolah Menengah Atas melalui Model Pembelajaran Generatif - Martunis Martunis; M. Ikhsan; Syamsul Rizal (Universitas Syiah Kuala, 2014)
The low ability of students' mathematical understanding and communication as well as the importance of both the enhanced capabilities require a learning model that provides the opportunity for students to construct their own knowledge, one of models is generative learning model. For this reason, researchers interested in conducting research on the application of generative learning model in mathematics learning activities. This study was an experimental study with quantitative approach aimed to obtain the increase in the ability of students' mathematical understanding and communication in mathematical learning using generative learning model reviewed based on the overall student and the student level. This study used a pretest-posttest design with a control group. Data collecting by using a test to determine the gain of ability students' mathematical understanding and communication. Based on analysis of the data concluded that (1) the increase of students mathematical understanding abilities which learning obtain by generative models better than the increase of students' mathematical understanding abilities taught by conventional learning reviewed by the overall student or student level, (2) the increase of students mathematical communication abilities taught by learning generative models better than the increase of students' mathematical communication abilities which taught conventional learning reviewed based on the overall student and the student level, (3) there is no interaction between the factors of the learning approach with the level of mathematical ability and the increase of students 'mathematical understanding, and (4) there is no interaction between factors learning approach and the level of students to the improvement of students' mathematical communication abilities.